2014
DOI: 10.1111/jfpe.12083
|View full text |Cite
|
Sign up to set email alerts
|

Production of High‐Aroma Instant Tea Powder Using Various Novel Technologies

Abstract: Various nonthermal processing technologies were applied, including pulsed electric field (PEF) technology, freeze concentration and vacuum freeze‐drying. The black tea was extracted with hot water extraction, cold extraction and PEF extraction. Results indicated that PEF‐assisted extraction had the best extraction efficiency for the main chemical components from tea at lower temperatures. Optimal PEF extraction conditions were achieved (tea leaves/water ratio of 1:16, electric field strengths of 20 kV/cm and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 13 publications
(18 reference statements)
0
11
1
Order By: Relevance
“…Studies have reported that the color and aroma of tea improves following ultrasonic and microwave treatments [29][30][31][32][33][34]. However, in this study, the aroma of tea after ultrasonic and microwave treatments increased and decreased, respectively.…”
Section: Sensory Evaluationcontrasting
confidence: 63%
“…Studies have reported that the color and aroma of tea improves following ultrasonic and microwave treatments [29][30][31][32][33][34]. However, in this study, the aroma of tea after ultrasonic and microwave treatments increased and decreased, respectively.…”
Section: Sensory Evaluationcontrasting
confidence: 63%
“…By using PEF for extraction, tea’s aromatic compounds, polyphenols are protected from damage [ 34 , 35 , 188 ], and its color, taste, and aroma remain unchanged [ 34 , 35 , 39 , 179 , 186 , 188 ]. Traditionally, PEF has been used in the extraction and retention of polyphenols from green tea [ 179 , 187 ], black tea [ 186 ], Puer tea [ 174 ], and green tea infusions [ 33 35 ]. PEF retained more bioactive compounds and color than conventional heat treatment [ 34 , 35 ].…”
Section: Innovative Methods Of Extractionmentioning
confidence: 99%
“…Most of the aroma compounds are low-polar volatile substances which were not effectively extracted by the traditional extraction methods using hot water or ethanol aqueous solution, or lost during the concentration of tea extracts at high temperatures (Zhu et al 2008;Huo et al 2014;Katsuno et al 2014). Some efforts have been made to extract or recover the tea aroma compounds in the production of instant tea, such as vacuum-distillation, simultaneous distillation and extraction, resin adsorption, supercritical extraction, microwave assisted extraction and freeze drying (Lv et al 2012;Ye et al 2014). These methods are ineffective or uneconomic for industrial production of instant green teas.…”
Section: Introductionmentioning
confidence: 99%